I03 Evaluation of life time physical activity levels in Huntington's disease. (29th August 2012) - Read, J; Owen, G; Keogh, R; Busse, M; Jauffret, C; Coleman, A; 't Hart, E; Borrowsky, B; Tabrizi, SJ; ,
Abstract : Background: Environmental factors may influence the onset and progression of neurodegenerative disorders, either directly or by interacting with genetic risk factors. Trembath and colleagues interviewed individuals with a formal clinical diagnosis of Huntington's disease (HD) and found that those who led a more passive lifestyle had an earlier age of onset than those who were less passive. 1 Aims: To establish the feasibility of using self-completion questionnaires to gather life time physical activity levels in a group of early stage and premanifest HD individuals from the TRACK-HD cohort so that this data could be compared to clinical outcomes in TRACK-HD study. Methods: A self-report questionnaire was developed based on the Leisure Time Exercise Questionnaire by Godin et al. 2 Activity levels were calculated across activities undertaken at home, at work and during recreation and for life stages from the teenage years, across each decade to the current age or age of disease onset. Life-time activity was categorised as strenuous, moderate or light, and activity scores were calculated from the frequency and duration of each activity. Results: Retrospective data were collected from 277 participants (89 controls, 109 premanifest gene carriers, 79 HD Stage I/II) and the data used to distinguish the most and least physically active individuals. Modes of activity were also investigated. Conclusions: Although retrospective data may be limited by recall bias, our data suggests that it is possible to use a general measure of life time physical activity levels. Such a life course perspective on physical activity may be a useful adjunct to the assessment of physical activity with more direct quantitative measures. References: 1. Trembath MK, et al. A retrospective study of the impact of lifestyle on age at onset of Huntington disease. Mov Disord 2010;25 :1444–50. 2. Godin G, Shephard RJ. Godin leisure time exercise questionnaire. Med Sci Sports Exerc 1997:S36–8.